The diagnostic value of metagenomic next-generation sequencing for identifying Pneumocystis jirovecii infection in non-HIV immunocompromised patients - Zhao, Mengyi; Yue, Ruiming; Wu, Xiaoxiao; Gao, Zhan; He, Miao; Pan, Lingai (Frontiers in Cellular and Infection Microbiology, 2022)
Background:Pneumocystis jirovecii pneumonia (PJP) remains an important cause of morbidity and mortality in non-HIV immunocompromised patients especially in transplant recipients. But its diagnosis remains challenging due to the insufficient performance of conventional methods for diagnosing (P. jirovecii infection. Therefore, the auxiliary diagnostic function of metagenomics next-generation sequencing (mNGS) in clinical practice is worth of exploring. Method:34 non-HIV immunocompromised patients who were diagnosed as PJP by clinical manifestations, imaging findings, immune status of the host, and Methenamine silver staining were tested by mNGS from October 2018 to December 2020 in Sichuan Provincial People's Hospital. The clinical performances of mNGS for P. jirovecii infection diagnosis were also evaluated with genome reads abundance and comparing with other traditiaonal diagnostic methods. Results:We diagnosed a total of 34 non-HIV PJP patients by the clinical composite diagnosis. Our data shows that, compared with the clinical microbiological test, the detection rate of mNGS for P. jirovecii in non-HIV infected PJP patients is significantly higher than that of Methenamine silver staining and serum 1-3-β-D-glucan. mNGS can be used as an auxiliary diagnostic tool to help diagnosis.The number ofreads mapped to the genome of P. jiroveciiand the duration of patients from onset to sampling collection were statistically significant between the two groups (Reads>100 and Reads≤100) (8days vs. 23days, p=0.020). In addition, univariate analysis showed that C-reactive protein (15.8mg/L vs.79.56mg/L, p=0.016), lactate dehydrogenase (696U/l vs. 494U/l, p=0.030) and procalcitonin (0.09ng/ml vs. 0.59ng/ml, p=0.028) was also statistically significant between the two groups. Conclusions: An effective detection rate was achieved in PJP patients using mNGS testing of bronchoalveolar lavage fluid (BALF) or blood.. The study also confirmed that the abundance of reads of P. jirovecii is related to the interval between the onset and sample collection. And the inflammation status during simultaneous mNGS detection might determine the abundance of pathogens. Hence, we conclude that the mNGS strategy could benefit disease diagnosis as well as treatment when complicated clinical infections appeared.